Interaksi Sosial Pendidikan dalam Pembelajaran Online - Nurifadilah Idrus; Sri Indah Lestari; Nuraini Nuraini; Sam'un Mukramin; Kameliyani Kameliyani (Journal on Education, 2023)
This article is entitled educational social interaction in online learning which aims to provide an overview to the wider community of the importance of social interaction, especially in the educational sphere when online learning is implemented in Islamic Religious Education, University of Muhammadiyah Makassar. The method used in the preparation of this article is descriptive qualitative with a purposive sampling approach based on certain criteria so that the data obtained is in accordance with the existing facts until it is known that when viewed from an educational perspective, the implementation of online learning reduces the educational function of students due to reduced interaction which results in on the learning quality of students such as lack of understanding of learning material, communication that can be interrupted because of the network, or more interested in online games than the learning material itself. And from a family perspective, online learning is able to strengthen the relationship between parents and children so that they can understand each other better because of the frequent interactions that occur.